Towards the Spirit of Renewal and Openess: The Roman Catholic Church Reforms and the Global South - Willem Leonardus Turpijn; William Cahyawan; Benny Suwito (Institute of International Studies, 2019)
The Second Vatican Council (1962-1965) has brought change into the Roman Catholic Church. Since that day, various changes has taken place within the Roman Catholic Church. Furthermore, the Roman Catholic Church which has always been associated with the Western world, especially European and North American countries, is and will face the